Fear of Childbirth: Wellbeing and Partner Support in First-time Pregnant Women - Anjum, Ambreen; Mushtaq, Mamoona; Anwar, Tahira; Ali, Muhammmad (Journal of Liaquat University of Medical & Health Sciences, 2023)
Objective: To assess the fear of childbirth, well-being and partner support in first-time pregnant women. Methodology: This Cross-sectional study included 100 participants selected by purposive sampling. The sample was collected from two Hospitals in Lahore (Lady Wallington Hospital and Hameed Lateef Hospital) from June to October 2019. Wijma Delivery Expectancy Questionnaire, Wellbeing in Pregnant Women Questionnaire and Partner Support Questionnaire was used to collect data. Analysis was completed using SPSS version 23. Pearson correlation was used to assess the relationship between study variables. An Independent sample t-test was used to compare study variables, and simple linear regression analysis was calculated to predict fear of childbirth on their perception of partner support. Results: 62% of first-time pregnant women showed fear of childbirth. Women who had more fear of childbirth had a low level of well-being (p<0.001). Partner support was significantly negatively correlated with fear of childbirth while positively correlated with well-being (r = .48, p < .001). Conclusion: Women with first pregnancy suffer from fear of childbirth. However, partner support is essential to overcome this fear and help increase first-time pregnant women’s well-being.